2003
DOI: 10.1136/vr.153.20.628
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Cryptosporidium parvum ‘cattle’ genotype from a severe outbreak of neonatal foal diarrhoea

Abstract: Intubation conditions were scored numerically such that 1 indicated good conditions, 2 indicated some difficulty (for example, swallowing, chewing, inability to widely open the jaws or difficulty in advancing the tube), and 3 indicated an aborted attempt. Overall, 38 pigs scored 1 for intubation con-Veterinary Record (2003)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0
2

Year Published

2007
2007
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 23 publications
1
23
0
2
Order By: Relevance
“…hominis, C. tyzzeri, C. felis, C. ubiquitum and C. andersoni (Grinberg et al, 2003;Xiao, 2010;Guo et al, 2014;Liu et al, 2015;Qi et al, 2015;Jian et al, 2016;Wagnerová et al, 2016). In the present study, only 293bp of clean sequence for the 18S locus was obtained and therefore further studies on a larger number of isolates at multiple loci are required to fully characterize the novel species from horses.…”
Section: Discussionmentioning
confidence: 72%
“…hominis, C. tyzzeri, C. felis, C. ubiquitum and C. andersoni (Grinberg et al, 2003;Xiao, 2010;Guo et al, 2014;Liu et al, 2015;Qi et al, 2015;Jian et al, 2016;Wagnerová et al, 2016). In the present study, only 293bp of clean sequence for the 18S locus was obtained and therefore further studies on a larger number of isolates at multiple loci are required to fully characterize the novel species from horses.…”
Section: Discussionmentioning
confidence: 72%
“…The variability in the primer sequences is the probable explanation for the failure in amplifying DNA. Though, in different regions of the world, Cryptosporidium infections have been reported in goats, rabbits (Marlier et al, 2003;Peeters, 1988;Shiibashi et al, 2006), horses (Browning et al, 1991;Darabus et al, 2001;Grinberg et al, 2003;Majewska et al, 1999;Majewsk et al, 2004;Olson et al, 1997), all examined animals in these species in Tunisia were not found to be infected with Cryptosporidium. The age of sampled animals as well as animal management practices or environmental conditions could explain such results.…”
Section: Discussionmentioning
confidence: 99%
“…Cryptosporidium is recognized as one of the main causes of diarrhea in lambs (de GRAAF et al, 1999), causing high morbidity and mortality and major economic losses (CASEMORE et al, 1997). In pigs and equines Cryptosporidium appear to be of less zoonotic importance, although diarrhea in post-weaning piglets and reduction in growth rate, food absorption and weight loss in equine have already been described (MISIC et al, 2003;GRINBERG et al, 2003).…”
Section: Discussionmentioning
confidence: 99%